Reliability in the Diagnosis of Personality Disorders and Criminal Responsibility - Deniz, Derya (The Bulletin of Legal Medicine, 2017)
The most striking aspect of the state power is the "right to punish" and the concept of "punishment" in that notion. The level of punishment is determined by the degree of intent and fault, and the level of the crime committed. The point that psychiatry assisting criminal law is whether or not the “mens rea” has taken place. The concept of "Criminal Responsibility" is clear and obvious for a mental health professional. A diagnosis about an acute or chronic mental illness can be proven in the legal sense. But the question here is not the diagnostic origin. It is to detect the functional reduction in legal or criminal responsibility. Judging from the practice of forensic psychiatry personality disorders - unlike some major mental illnesses - are generally not seen as a phenomenon that dispose criminal responsibility. Of course, criminal behavior is not merely due to personality disorders. Research findings indicate that personality disorders are caused by the interaction of environmental conditions and poorly life experiences as well as genetic vulnerability. Are these genetic factors or other factors reducing the criminal responsibility of a person? What should be discussed here is the functionality of the criteria used in the moral/mental assessment process for criminal responsibility of suspects with personality disorder. From the judicial process point of view, the most important instrument that a psychiatrist has in diagnosis is classification. Although some of them are defined by DSM IV, it is known that none of the personality disorders criteria could be fully settled today. The DSM system does not provide information on dysfunctions caused by partial diseases, so the related diagnoses can not solve judicial problems in legal cases. In such a case, how will it be decided whether the ability to comply with social norms has been reduced by personality disorders?
Keywords: personality disorders; criminal act; criminal responsibility; forensic psychology